Efficacy and potency of lichens of Mizoram as antimycotic agents - and D.K. UPRETI, AMRITESH C. SHUKLA*, M. CHINLAMPIANGA, ARCHANA VERMA, ANUPAM DIKSHIT (Indian Phytopathology, 2012)
Antifungal property of aqueous and acetone extracts of two lichens was investigated against plant pathogenic fungi viz., Alternaria alternata, Aspergillus flavus and Penicillium italicum shows strong efficacy against the test fungi. Acetone extracts of both the lichen spp. were more effective than aqueous extracts. Aqueous and acetone extracts of Stereocaulon sp. were more effective than Ramalina sp. The aqueous and acetone extracts of Ramalina sp. and Stereocaulon sp. at 50 Î¼l/ml concentration contains broad fungi toxic spectrum. Based on these findings as well as after detailed in vitro investigations, the active constituents of lichens can be synthesized and used as a potential substitute of synthetic fungicides.